(1-x*x*x)*(3x*x-5z)=

Simple and best practice solution for (1-x*x*x)*(3x*x-5z)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1-x*x*x)*(3x*x-5z)= equation:


Simplifying
(1 + -1x * x * x)(3x * x + -5z) = 0

Multiply x * x
(1 + -1x2 * x)(3x * x + -5z) = 0

Multiply x2 * x
(1 + -1x3)(3x * x + -5z) = 0

Multiply x * x
(1 + -1x3)(3x2 + -5z) = 0

Multiply (1 + -1x3) * (3x2 + -5z)
(1(3x2 + -5z) + -1x3 * (3x2 + -5z)) = 0
((3x2 * 1 + -5z * 1) + -1x3 * (3x2 + -5z)) = 0
((3x2 + -5z) + -1x3 * (3x2 + -5z)) = 0
(3x2 + -5z + (3x2 * -1x3 + -5z * -1x3)) = 0

Reorder the terms:
(3x2 + -5z + (5x3z + -3x5)) = 0
(3x2 + -5z + (5x3z + -3x5)) = 0

Reorder the terms:
(3x2 + 5x3z + -3x5 + -5z) = 0
(3x2 + 5x3z + -3x5 + -5z) = 0

Solving
3x2 + 5x3z + -3x5 + -5z = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 2.25a-7.5=21 | | 3(2x+4)=6(x+3) | | a=1500(1+0.067)27 | | -20=-11s+4 | | 8g-7+2g=13 | | 5x+1=2x-9 | | 3cos^2x=3-cos^2x | | 4x+1=15+2x | | 4y^2+34y=-144 | | -6x-28+8x=14 | | 20-2P=-10+4P | | [8+5y]=14 | | 3.5x+-20+.5x=40-2x | | -7=6-C | | 7x+5x-65=79 | | 9y=5x-7 | | 5x+8y+4xy= | | Y=24x+15 | | 4x+2=-25 | | 27-9x+15y=0 | | 4cosx+2=cosx+1 | | 6-9p-2= | | 3ln(x-2)+6=7 | | y+2-3y=-18 | | 5x+8=5(x+2) | | 10x-35=3x-7 | | 8x-16=7x+4 | | 2(4x-5)=17 | | 50x-2y=50 | | -86+11x-2x=121 | | 3p+8+2p=28 | | 9x+6x-91=104 |

Equations solver categories